Orf Virus-Based Vectors Preferentially Target Professional Antigen-Presenting Cells, Activate the STING Pathway and Induce Strong Antigen-Specific T Cell Responses - Müller, Melanie; Reguzova, Alena; Löffler, Markus W.; Amann, Ralf (Frontiers in Immunology, 2022)
Background: Orf virus (ORFV)-based vectors are attractive for vaccine development as they enable the induction of potent immune responses against specific transgenes. Nevertheless, the precise mechanisms of immune activation remain unknown. This study therefore aimed to characterize underlying mechanisms in human immune cells. Methods: Peripheral blood mononuclear cells were infected with attenuated ORFV strain D1701-VrV and analyzed for ORFV infection and activation markers. ORFV entry in susceptible cells was examined using established pharmacological inhibitors. Using the THP1-Dual™ reporter cell line, activation of nuclear factor-B and interferon regulatory factor pathways were simultaneously evaluated. Infection with an ORFV recombinant encoding immunogenic peptides (PepTrio-ORFV) was used to assess the induction of antigen-specific CD8+ T cells. Results: ORFV was found to preferentially target professional antigen-presenting cells (APCs) in vitro, with ORFV uptake mediated primarily by macropinocytosis. ORFV-infected APCs exhibited an activated phenotype, required for subsequent lymphocyte activation. Reporter cells revealed that the stimulator of interferon genes pathway is a prerequisite for ORFV-mediated cellular activation. PepTrio-ORFV efficiently induced antigen-specific CD8+ T cell recall responses in a dose-dependent manner. Further, activation and expansion of naïve antigen-specific CD8+ T cells was observed in response. Discussion: Our findings confirm that ORFV induces a strong antigen-specific immune response dependent on APC uptake and activation. These data support the notion that ORFV D1701-VrV is a promising vector for vaccine development and the design of innovative immunotherapeutic applications.